2008
DOI: 10.1212/01.wnl.0000334751.89859.7f
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, controlled, dose-ranging trial of carisbamate for partial-onset seizures

Abstract: Carisbamate at doses of 300, 800, and 1,600 mg/d was effective as adjunctive therapy for reducing the frequency of partial-onset seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
48
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 9 publications
7
48
1
1
Order By: Relevance
“…Despite its disparity with previous preclinical work, the equivocal antiepileptic effect of CRS we found in rpFPI-PTE was not inconsistent with that observed in populations of partial-onset pharmacoresistant epilepsy patients in add-on clinical trials (Faught et al, 2008;Sperling et al, 2010), because large effects of CRS were not seen in either case. No clinical data are available to assess the performance of CRS on patients with pharmacoresistant epilepsy caused by head trauma, and neither our study nor the add-on clinical trials of CRS in pharmacoresistant epilepsies may reflect the performance of CRS on pharmacoresponsive epilepsy patients.…”
contrasting
confidence: 99%
“…Despite its disparity with previous preclinical work, the equivocal antiepileptic effect of CRS we found in rpFPI-PTE was not inconsistent with that observed in populations of partial-onset pharmacoresistant epilepsy patients in add-on clinical trials (Faught et al, 2008;Sperling et al, 2010), because large effects of CRS were not seen in either case. No clinical data are available to assess the performance of CRS on patients with pharmacoresistant epilepsy caused by head trauma, and neither our study nor the add-on clinical trials of CRS in pharmacoresistant epilepsies may reflect the performance of CRS on pharmacoresponsive epilepsy patients.…”
contrasting
confidence: 99%
“…In these clinical trials, carisbamate demonstrated a good central nervous system (CNS) side effect profile, with mild to moderate dose-dependent somnolence and dizziness when given adjunctively with two or three concomitant antiepileptic drugs. Similarly, discontinuation rates due to CNSrelated adverse effects were relatively low, and were highest (19%) at the maximal dose tested (i.e., 1600 mg/day) [15]. When given as monotherapy in a migraine prophylaxis trial that failed to show efficacy, carisbamate was also well tolerated at doses up to 600 mg/day [17].…”
Section: Introductionmentioning
confidence: 92%
“…It also has been shown to attenuate alcohol intake in animals [2,14]. In human investigations in patients with epilepsy, carisbamate (200-1600 mg/day) has shown antiepileptic efficacy in some but not all studies [15,16]. In these clinical trials, carisbamate demonstrated a good central nervous system (CNS) side effect profile, with mild to moderate dose-dependent somnolence and dizziness when given adjunctively with two or three concomitant antiepileptic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…2-4 Although there was a trend for better seizure control with higher doses of carisbamate, given the dose-related reduction in tolerability, carisbamate is no longer being evaluated for this indication. [2][3][4] Pharmacokinetic (PK) studies in humans indicate carisbamate is rapidly absorbed with mean peak plasma concentrations observed around 0.5 to 2 hours following a single oral dose of 500 mg. 5 Oral bioavailability was estimated to be approximately 94%. 6 Coadministration with food does not alter the PK of carisbamate to a clinically relevant level.…”
mentioning
confidence: 99%
“…1 In 4 doubleblind, placebo-controlled studies in adult patients with partial-onset seizures that have been conducted to date, carisbamate failed to consistently demonstrate a significant treatment difference relative to placebo across the dose ranges assessed. [2][3][4] Although there was a trend for better seizure control with higher doses of carisbamate, given the dose-related reduction in tolerability, carisbamate is no longer being evaluated for this indication. [2][3][4] Pharmacokinetic (PK) studies in humans indicate carisbamate is rapidly absorbed with mean peak plasma concentrations observed around 0.5 to 2 hours following a single oral dose of 500 mg. 5 Oral bioavailability was estimated to be approximately 94%.…”
mentioning
confidence: 99%